Pengaruh Karakterisik Bank Terhadap Capital Adequacy Ratio (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
Capital adequacy is an important part of a company's financial performance, because achieving an optimal capital adequacy ratio (CAR) indicates that the company has sufficient capital to fund each of its operations. Sufficient capital allows the company to easily innovate, so that it can develop the company's productivity. Interestingly, CAR is influenced by various factors, so it is necessary to study academically the factors that influence CAR. The purpose of this study is to determine the factors that influence CAR. This study uses a quantitative approach with empirical methods using Bank BTN data for the 2010-2020 period. The results show that this model contributes 81% to changes in CAR, partially showing that ROA has a negative effect on CAR, meaning that the lower the ROA, the higher the CAR, LDR has a negative effect on CAR, meaning that the lower the LDR, the higher the CAR, and the NPL has an effect negative to CAR means that the lower the NPL, the higher the CAR. This indicates that increases or decreases in ROA, LDR, and NPL have an impact on changes in CAR at Bank BTN.